NUTRIENT DENSITY COOKIES RUTF (READY TO USE THERAPEUTIC FOOD) DARI PANGAN LOKAL UNTUK INTERVENSI BALITA WASTING - Ria Ambarwati; Vera Asti Rahmawati; Fitriani Fitriani (Department of Nutrition Science, Faculty of Medicine, Universitas Diponegoro, 2023)
ABSTRACT Background: Ready to Use Therapeutic Food (RUTF) is recommended in giving interventions to toddlers with uncomplicated wasting. Kepok banana (Musa paradisiaca L) and peanuts (Arachis hypogaea L) are local food ingredients that are easily available and processed into RUTF as an alternative to RUTF-WHO.Purpose: Developing RUTF from local food with nutrient density that meets RUTF-WHO standards, and has organoleptic characteristics that are acceptable to toddlers.Methods: Experimental research with completely randomized design with 2 repetitions. The research was divided into three stages, namely developing RUTF cookies with the main ingredient kepok banana flour with variations of peanut substitution 100 grams, 125 grams and 150 grams, nutritional value analysis, acceptance testing using 25 somewhat trained panelists and 20 toddlers aged 2-5 year. Analysis of nutritional value data was tested by ANOVA, the acceptance test of somewhat trained panelists was tested by Friedman and the acceptance test on toddlers was analyzed descriptively.Results: The higher the substitution of peanuts increased the levels of energy, protein, fat, and carbohydrates in RUTF cookies (per 100 grams), however, it could not reach the RUTF-WHO standard. The higher the substitution of peanuts, the higher the distinctive aroma and taste of peanuts, the texture is not too crunchy, and the color is darker. There was no difference in the acceptability of cookie panelists under five RUTF F1 and F2.Conclusion: RUTF Cookies F1 and F2 can be recommended as variations of RUTF. Further research is needed by modifying the amount and composition of ingredients to increase the energy, fat and carbohydrate levels of RUTF cookies. Keywords: Cookies; Kepok banana; Peanuts; RUTF.ABSTRAKLatar Belakang: Ready to Use Therapeutic Food (RUTF) direkomendasikan dalam pemberian intervensi pada balita wasting tanpa komplikasi. Pisang kepok (Musa paradisiaca L) dan kacang tanah (Arachis hypogaea L) merupakan bahan pangan lokal yang mudah didapatkan dan diolah menjadi RUTF sebagai alternatif pengganti RUTF-WHO.Tujuan: Mengembangkan RUTF dari pangan lokal dengan densitas zat gizi yang memenuhi standar RUTF-WHO, serta memiliki karakteristik organoleptik yang dapat diterima oleh balitaMetode: Penelitian eksperimen dengan desain Rancangan Acak Lengkap 2 kali ulangan. Penelitian terbagi menjadi tiga tahap, yaitu pengembangan cookies RUTF dengan bahan utama tepung pisang kepok dengan variasi substitusi kacang tanah 100 gram, 125 gram dan 150 gram, analisis nilai gizi, pengujian daya terima menggunakan 25 panelis agak terlatih dan 20 balita usia 2 – 5 tahun. Analisis data nilai gizi diuji dengan ANOVA, Uji daya terima panelis agak terlatih diuji dengan Friedman dan uji daya terima pada balita dianalisis secara deskriptif.Hasil: Semakin tinggi substitusi kacang tanah meningkatkan kadar energi, protein, lemak, dan karbohidrat cookies RUTF (per 100 gram), akan tetapi belum dapat mencapai standar RUTF-WHO. Semakin tinggi substitisi kacang tanah memberikan aroma dan rasa khas kacang tanah yang lebih tinggi, tekstur yang tidak terlalu renyah, dan warna yang lebih gelap. Tidak terdapat perbedaan daya terima panelis balita cookies RUTF F1 dan F2.Simpulan : Cookies RUTF F1 dan F2 dapat direkomendasikan sebagai variasi RUTF. Perlu penelitian lanjutan dengan melakukan modifikasi jumlah maupun komposisi bahan untuk meningkatkan kadar energi, lemak dan karbohidrat cookies RUTFKata Kunci: Cookies; Kacang tanah; Pisang kepok; RUTF.